2020
DOI: 10.1016/j.cjco.2020.05.001
|View full text |Cite
|
Sign up to set email alerts
|

Percutaneous Left Ventricular Assist Device in Cardiogenic Shock: A Five-Year Single Canadian Center Initial Experience

Abstract: Background Mechanical circulatory support in cardiogenic shock (CS) with percutaneous left ventricular assist devices (PVADs) has expanded rapidly, but there is a paucity of Canadian data. Conflicting observational reports have emerged regarding the benefit of PVADs in CS. We describe a 5-year experience with Impella CP for CS at a single Canadian tertiary care centre. Methods Consecutive adult patients with CS supported with Impella CP were included. Comprehensive clin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 35 publications
0
7
0
Order By: Relevance
“…From 4173 articles, we reviewed 206 full-text articles. In total, we included 71 studies (63 observational, 8 PSM/RCTs) detailing 4280 adult patients that reported on the use of microaxial LVADs in CS ( Figure 1 ) [ 16 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 , 79 , 80 , 81 , 82 , 83 , 84 , 85 , 86 , 87 , 88 , 89 , 90 , 91 , 92 , 93 …”
Section: Resultsmentioning
confidence: 99%
“…From 4173 articles, we reviewed 206 full-text articles. In total, we included 71 studies (63 observational, 8 PSM/RCTs) detailing 4280 adult patients that reported on the use of microaxial LVADs in CS ( Figure 1 ) [ 16 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 , 79 , 80 , 81 , 82 , 83 , 84 , 85 , 86 , 87 , 88 , 89 , 90 , 91 , 92 , 93 …”
Section: Resultsmentioning
confidence: 99%
“…Some studies indicate that patients in SCAI stage C or D tend to experience the greatest advantages with an earlier use of a percutaneous LVAD (pLVAD). 33 Others studies suggest to wait until there is evidence of deterioration to avoid subjecting patients prematurely to the potential complications associated with MCS. 34 Hence, optimal timing of MCS remains elusive, which may explain the similar usage rates of MCS across SCAI shock stages C, D, and E in this study (which importantly enrolled patients treated before publication of the ECLS-SHOCK results).…”
Section: Treatments In Different Types Of Heart Failure-related Cardi...mentioning
confidence: 99%
“…While studies have shown the benefits of MCS in such patients, the optimum timing of intervention remains controversial, with recent studies indicating that early initiation of MCS is warranted and delays lead to higher chances of mortality. [6,7] e commonly used MCS in cardiogenic shock (summarized in Table 1) include-IABP IABP was the first MCS device designed and used, and it is also the most used device. It is deployed using common femoral artery access, and placed in the descending aorta, 2 cm below the left subclavian artery.…”
Section: Mcs In Cardiogenic Shockmentioning
confidence: 99%